Comparative Analysis Of Chaotic Cat MAP And Fibonacci Image Scrambling Methods To Secure Digital Image: Comparative Analysis Of Chaotic Cat MAP And Fibonacci Image Scrambling Methods To Secure Digital Image - Hendra Hendra; Johanus Kurniawan; Insidini Fawwaz (Institute of Computer Science (IOCS), 2020)
In the process of communication through the internet network, security is an important issue that needs serious attention. This is because the process of sending and communicating data through the internet has the possibility to be intercepted by other parties. This also applies to image data. Therefore, data to be sent via the internet must be secured first. However, the application of several cryptographic methods and several methods of randomization of images requires a relatively long time. To solve the problems encountered, the Image Scrambling Generalized Fibonacci And Chaotic Cat Map algorithm can be applied. The work process of the algorithm will start from the process of selecting the input image and charging the key value that will be used. After that, the process continues with the process of randomizing the image, so that it will produce a randomized image. The resulting image can be reconstructed again by applying an anti-scrambling algorithm. This process requires the same key to be used at the scrambling stage. The resulting application can randomize the original image by filling in the randomization key value. The resulting image can be reconstructed again using the same key. In addition, the application will also produce detailed reports of calculations performed during the scrambling and anti-scrambling processes for each of these methods.